The Implementation of Curriculum 2013 for French Subject Based on Phenomenological Perspective: Implementasi Kurikulum 2013 Mata Pelajaran Bahasa Prancis Berdasarkan Sudut Pandang Fenomenologi - Ekowati, Sri Harini; Farisi, Salman Al (Politeknik Harapan Bangsa Surakarta, 2022)
The curriculum 2013 (K.13) has been applied since 2013, but its implementation in the French language teaching at high school has not been widely studied. This study aims to determine the implementation of K.13 in French language teaching at high school. This study is a qualitative research with phenomenological approach involving four French teachers: 2 senior teachers and 2 junior teachers. The data are obtained through interviews and analysed using Miles and Huberman theory. The results showed that those four French teachers had implemented K.13 in their classrooms. Likewise, there are some teachers who have applied scientific approach, PBL, discovery learning, and PjBL.